Kawih Asuh Barudak: Innovative Media of Sunda Learning in Elementary School - Hendrayana, Dian; Suherman, Agus (International Conference on Elementary Education, 2020)
For a long time elementary school students in West Java did not have songs based on education and character development. Therefore, students often sing songs belonging to adults who are not intended. Lately Kawih Asuh Barudak material has appeared in the educational environment. The purpose of this study is to explain how the material of Kawih Asuh Barudak is used for learning Sundanese in elementary schools. Kawih Asuh Barudak are Sundanese songs containing moral messages such as strengthening piety, respect for parents, love for the environment, love for others, knowledge, character, and love for the motherland; packed with musical compositions that are lightweight and easy to learn. The results obtained are, 1) students prefer to absorb learning material with innovative, creative, interactive, and enjoy; 2) students prefer to follow learning material by singing method which is more fun than lecture method; and 3) students are easier to absorb applicable learning material than theoretical and rote learning. Therefore, language learning methods through media with kawih material are seen as alternatives to innovative learning media